Sensitivity of Fetal RhD Screening for Safe Guidance of Targeted Anti–D Immunoglobulin Prophylaxis: Prospective Cohort Study of a Nationwide Programme in the Netherlands. Issue 3 (March 2017) - de Haas, Masja; Thurik, Florentine F.; van der Ploeg, Catharina P. B.; Veldhuisen, Barbera; Hirschberg, Hoang; Soussan, Aicha Ait; Woortmeijer, Heleen; Abbink, Frithjofna; Page-Christiaens, Godelieve C. M. L.; Scheffer, Peter G.; van der Schoot, C. Ellen
Abstract : (Abstracted from BMJ 2016;355:i5789) The risk of maternal alloimmunization due to RhD incompatibility has decreased with use of antenatal and postnatal anti–D immunoglobulin prophylaxis. The discovery of cell-free fetal (cff) DNA in maternal plasma during pregnancy and the feasibility of fetal RhD testing using this source of DNA make it possible to determine fetal RhD type and to restrict the use of antenatal anti–D immunoglobulin to only those RhD-negative women carrying an RhD-positive fetus.